2020
DOI: 10.1097/gme.0000000000001539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chinese herbal medicine on serum lipids in postmenopausal women with mild dyslipidemia: a randomized, placebo-controlled clinical trial

Abstract: Objective: Previous studies have shown the association between menopause and dyslipidemia. This study was aimed to evaluate the effect of Chinese herbal medicine, tonifying kidney and descending turbidity (TKDT) granule, on serum lipid profiles in postmenopausal women with dyslipidemia. Methods: A double-blind randomized, placebo-controlled trial was conducted among 104 postmenopausal Chinese women with mild dyslipidemia. Participants were randomized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, the data overall do not support the use of MHT for the primary prevention of cardiovascular disease ( 30 – 32 ). A previous study indicated that TKRDF reduced the lipid profile in Chinese postmenopausal women with mild dyslipidemia ( 10 ). However, the underlying mechanism of how TKRDF treats postmenopausal dyslipidemia remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data overall do not support the use of MHT for the primary prevention of cardiovascular disease ( 30 – 32 ). A previous study indicated that TKRDF reduced the lipid profile in Chinese postmenopausal women with mild dyslipidemia ( 10 ). However, the underlying mechanism of how TKRDF treats postmenopausal dyslipidemia remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is used extensively in clinical practice. A previous study indicated that TKRDF granules could improve the lipid profile and reduce the related metabolic abnormalities in postmenopausal women with mild dyslipidemia when combined with lifestyle changes ( 10 ). However, the therapeutic mechanism by which TKRDF improves postmenopausal dyslipidemia is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Epimedium brevicornum Maxim can significantly increase BMD (98). In addition, individual RCTs have found that Chinese herbal medicines including compound capsules, granules, and oral herbal decoctions have benefits in alleviating hot flashes, depression, and menopausal symptoms (99,100). However, there is still insufficient data from large systematic reviews to conclude that Chinese herbal medicines are more effective than a placebo or HT (101,102).…”
Section: Complementary and Alternative Therapiesmentioning
confidence: 99%